BIODEGRADATION OF POLYSTYRENE BY PLASTIVORES GREATER WAXWORMS LARVAE (Galleria mellonella). - Abbas, T . K.,; H. S. Abdulhay, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to find and test biological methods for reducing the aggregation of plastics such as PS in the environment  and study the ability of Greater Wax worms larvae (Galleria mellonella) to eat PS that similar in the its structure to beeswax .Weight loss, morphology changes ,FTIR spectroscopy  and GC-mass analysis were performed which showed changes in chemical properties of the PS due to degradation. In this study  the percentage of weight loss was 33% in the PS treated with G. mellonella. FTIR of PS frass showed the disappearance of aromatic cycle band that was found in the origin PS at region more than 3000 cm-1. Also The PS frass samples from wax worms larvae revealed the creation of a new O-H stretching alcohols group or glycol substance at absorbance peak 3293cm-1 that no found in the origin PS that ensure the degradation of PS by wax worm larvae.